The Effect of Manalagi and Fuji Apple Juice on Triglyceride Level in Elderly - Rizki Dwi Agustin Harsono; Yulia Lanti Retno Dewi; Anik Lestari (AIBPM Publisher, 2021)
The purpose of this study is to determine effect of manalagi and fuji apples juice on triglyceride levels in in elderly. This study is an experimental study conducted on 39 elderly for 14 days, divided into 3 groups through randomized pre-post test control group design. G-0 was the control group, G-1 was the intervention group administered with manalagi apple juice, and G-2 was the intervention group given fuji apple juice. The data obtained were analyzed using Kruskal-Wallis and Mann-Whitney test. Trygliceride levels in the G-0 increased, whereas the G-1 and G-2 decreased. There was a significant difference (P